COVID-19 Vaccination Associated With Reduced Postoperative SARS-CoV-2 Infection and Morbidity. Issue 1 (19th January 2022) - Prasad, Nikhil K.; Lake, Rachel; Englum, Brian R.; Turner, Douglas J.; Siddiqui, Tariq; Mayorga-Carlin, Minerva; Sorkin, John D.; Lal, Brajesh K.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The purpose of this study was to determine the effect of COVID-19 vaccination on postoperative mortality, pulmonary and thrombotic complications, readmissions and hospital lengths of stay among patients undergoing surgery in the United States. Background: While vaccination prevents COVID-19, little is known about its impact on postoperative complications. Methods: This is a nationwide observational cohort study of all 1, 255 Veterans Affairs facilities nationwide. We compared patients undergoing surgery at least 2 weeks after their second dose of the Pfizer BioNTech or Moderna vaccines, to contemporary propensity score matched controls. Primary endpoints were 30-day mortality and postoperative COVID-19 infection. Secondary endpoints were pulmonary or thrombotic complications, readmissions, and hospital lengths of stay. Results: 30, 681 patients met inclusion criteria. After matching, there were 3, 104 in the vaccination group (1, 903 received the Pfizer BioNTech, and 1, 201 received the Moderna vaccine) and 7, 438 controls. Full COVID-19 vaccination was associated with lower rates of postoperative 30-day COVID-19 infection (Incidence Rate Ratio and 95% confidence intervals, 0.09 [0.01, 0.44]), pulmonary complications (0.54 [0.39, 0.72]), thrombotic complications (0.68 [0.46, 0.99]) and decreased hospital lengths of stay (0.78 [0.69, 0.89]). Complications were also low in vaccinated patients who tested COVID-19 positive before surgery but events were too few to detect a significant difference compared to controls. Conclusion: COVID-19 vaccination is associated with lower rates of postoperative morbidity. The benefit is most pronounced among individuals who have never had a COVID-19 infection before surgery.